Thermodynamics of sodium dodecyl sulfate (SDS) micellization: An undergraduate laboratory experiment - Marcolongo, Juan Pablo (2011)
An undergraduate laboratory experiment is presented that allows a thermodynamic characterization of micelle formation of sodium dodecyl sulfate (SDS) in aqueous solutions. The critical micelle concentration (CMC) and the degree of micelle ionization (α) are obtained at different temperatures by conductimetry. The molar standard free energy (ΔmicḠ), enthalpy (ΔmicH̄°), and entropy (Δ micS̄°) for the micellization process are calculated using the CMC, α, and their temperature dependences within the framework of a simplified model, the closed association model, which assumes an equilibrium between free surfactant monomers and monodispersed micelles. On the basis of hydration phenomena of surfactant molecules, a physicochemical discussion of the results is also proposed.